Synthesis and Characterization of g-C3N4/ZnO Nanocomposites for Gas Sensing Application. Issue 1 (1st January 2022) - Yethukrishnan, C.S; Vangari, Govind A.; Simon Patrick, D; Krishna Mohan, M.
Abstract: Air pollution is one of the prevailing issues in our atmosphere, which greatly affects humans and causes dangerous diseases. Toxic and green gases (NO2, CO2, NOx, H2 S, CO, Sulphur dioxide, and CH4 ) are present in the ambient atmosphere arising from different industries, vehicles, and fossil fuel combustion. g-C3 N4 /ZnO nanocomposites were prepared via a facile hydrothermal method. The synthesized g-C3N4/ZnO samples were analyzed using FE-SEM for morphological analysis and structural parameters are confirmed by XRD. Further investigation is done on sensing films for toxic gases by varying temperature, resistance change, and gas type.